2020
DOI: 10.1016/j.spl.2019.108656
|View full text |Cite
|
Sign up to set email alerts
|

On a loss-based prior for the number of components in mixture models

Abstract: We propose a prior distribution for the number of components of a finite mixture model. The novelty is that the prior distribution is obtained by considering the loss one would incur if the true value representing the number of components were not considered. The prior has an elegant and easy to implement structure, which allows to naturally include any prior information one may have as well as to opt for a default solution in cases where this information is not available. The performance of the prior, and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…The results are reported in Table 6 . We notice that according to the computed index, we identify as best model the mixture with components, which is in line with [ 16 ], and slightly more conservative than [ 15 , 16 ], where the number of components with non-zero weight is 5. Table 7 shows the posterior means for the parameters of the 4 components estimated.…”
Section: Mixture Modelssupporting
confidence: 70%
See 1 more Smart Citation
“…The results are reported in Table 6 . We notice that according to the computed index, we identify as best model the mixture with components, which is in line with [ 16 ], and slightly more conservative than [ 15 , 16 ], where the number of components with non-zero weight is 5. Table 7 shows the posterior means for the parameters of the 4 components estimated.…”
Section: Mixture Modelssupporting
confidence: 70%
“…To support a particular theory about the formation of galaxies, the analysis aims to estimate the number of stellar populations. This is a benchmark data set, well investigated in the literature, for example in [ 14 , 15 , 16 ], among others. We consider the galaxies velocities as random variables distributed according to a mixture of k normal densities.…”
Section: Mixture Modelsmentioning
confidence: 99%
“…We propose the three-parameter beta-negative-binomial distribution as a prior on the number of components K which unifies priors proposed in Richardson and Green (1997); Nobile (2004); Cerquetti (2010); Miller and Harrison (2018); Grazian et al (2020). Building on Antoniak (1974); Nobile (2004); Gnedin and Pitman (2006), we derive the implicitly induced prior on the number of clusters K + for generalized MFMs.…”
Section: Introductionmentioning
confidence: 97%
“…As part of the analysis, it is necessary to define prior distributions for all the parameters in the model, describing the prior knowledge the experimenter has about them. We have decided to use the default prior proposed in Grazian et al (2018) for the number of components since it has been shown to have a good balance between conservativeness and accuracy and standard vague priors for the rest of the parameters as in Richardson and Green (1997), in order to reduce the influence of the prior on the posterior distribution. Bayesian estimation of mixture models is a non-standard problem, therefore Monte Carlo Markov chains (MCMC) methods are needed to approximate the posterior distribution (Robert and Casella, 2013…”
Section: The Proposed Modelsmentioning
confidence: 99%